(3eQjV Gdhges - (3GHf egfj, bGSes ((3HjQhJs (3GdeSJbHd GdQbeis, 2017)
(3Je EYOGO bUU GdeSJhi GdSGOS ddbQGA hGdTHGH GdjGaYjf HgOa EZfGA KQhJge GddZhjI hJWhjQ CSdhHge GdcJGHj hGcJTGa eJYI GdJPhb GdCOHj ddJQGK GdYQHj, JYJeO gPg GdbUU Ydi QShe LPGHI edhfI hfUhU COHjI eeJYI oeTcdI JTcjdkG JGekG, HGdEVGaI Edi bGehS bje aj fgGjJgG MjK JJfGhd cd bUI EMOi Gdbje GdCNdGbjI hGdYHQ GdGLJeGYjI GdgGeI aj MjGI GdeQA, hGdeSJeOI ef JQGKfG GdYQHj ddGSJaGOI efgG hJYRjRgG aj hLOGf LjdfG GdUGYO hPGcQJg, cGdhaGA HGdYgO hGdYOd hZjQgGs
(3GdbUU GdYQHjIs
3 4
Keywords: (3GdbUU GdYQHjI GdbUjQIs -- (3eUQs